2011
DOI: 10.7589/0090-3558-47.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Salmonella in Australian Reptiles

Abstract: , 504 reptiles of four families and 57 species were examined for Salmonella by using cloacal or intestinal swabs. Salmonella was identified in 139 (28%) of the 504 animals tested. Of the 504 reptiles examined, 210 were captive and 294 were wild. Ninety-eight (47%) of the captive reptiles were shedding Salmonella at the time of sampling. In contrast, only 41 (14%) of the wild reptiles were shedding Salmonella. The higher prevalence of Salmonella in captive reptiles was statistically significant (P,0.0001). No S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 25 publications
(23 reference statements)
9
57
2
Order By: Relevance
“…from wildlife is not uncommon, and prevalences similar to or higher than the 4.661.7% we observed have been reported for a range of avian, reptilian, and mammalian species (Quessy and Messier 1992;Handeland et al 2002;Renter et al 2006;Phalen et al 2010;Scheelings et al 2011). Six of the seven isolates in this study were identified as Salmonella Mississippi (Edwards et al 1943).…”
Section: Discussionsupporting
confidence: 85%
“…from wildlife is not uncommon, and prevalences similar to or higher than the 4.661.7% we observed have been reported for a range of avian, reptilian, and mammalian species (Quessy and Messier 1992;Handeland et al 2002;Renter et al 2006;Phalen et al 2010;Scheelings et al 2011). Six of the seven isolates in this study were identified as Salmonella Mississippi (Edwards et al 1943).…”
Section: Discussionsupporting
confidence: 85%
“…None of the samples in this study were positive to Salmonella sp., otherwise very frequent finding in snakes (KUROKI et al, 2013;SCHEELINGS et al, 2011;STING et al, 2013;LUKAC et al, 2015) and a common cause of disease in humans. Low incidence of Salmonella was also described by SCHMIDT et al (2014) who reported 14.3% (8/56) Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…That fact hampers research efforts unless the clinical threats occur (Mihalca et al 2010;Sting et al 2013). Definitely, wildlife snakes carry a broad range of bacteria and parasites that differs considerably by geographical locations and source species (Borkovcová and Kopřiva 2005;Fitzgerald et al 2013;Hacioglu and Tosunoglu 2014;Lukac et al 2015;Scheelings et al 2011;Schmidt et al 2014;Shimalov and Shimalov 2000). Salmonella spp., being considered natural component of reptile gut flora, is one of the most frequently noted (Goupil et al 2012;Kuroki et al 2013;Prapasarakul et al 2012;Richards et al 2004;Scheelings et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Definitely, wildlife snakes carry a broad range of bacteria and parasites that differs considerably by geographical locations and source species (Borkovcová and Kopřiva 2005;Fitzgerald et al 2013;Hacioglu and Tosunoglu 2014;Lukac et al 2015;Scheelings et al 2011;Schmidt et al 2014;Shimalov and Shimalov 2000). Salmonella spp., being considered natural component of reptile gut flora, is one of the most frequently noted (Goupil et al 2012;Kuroki et al 2013;Prapasarakul et al 2012;Richards et al 2004;Scheelings et al 2011). Wildlife snakes are often reported as host of new parasites or record their new geographical location (Borkovcová and Kopřiva 2005;Halajian et al 2013;Santoro et al 2011;Shimalov and Shimalov 2000;Yildirimhan et al 2007).…”
Section: Introductionmentioning
confidence: 99%